2021
DOI: 10.1371/journal.pone.0259557
|View full text |Cite
|
Sign up to set email alerts
|

The association between self-reported stress and cardiovascular measures in daily life: A systematic review

Abstract: Background Stress plays an important role in the development of mental illness, and an increasing number of studies is trying to detect moments of perceived stress in everyday life based on physiological data gathered using ambulatory devices. However, based on laboratory studies, there is only modest evidence for a relationship between self-reported stress and physiological ambulatory measures. This descriptive systematic review evaluates the evidence for studies investigating an association between self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 80 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…Prior work, however, has shown inconsistent correlations between traditional (trait) math anxiety and various measures of in-the-moment ('state') anxiety about math 49 . Additionally, there is debate about the utility of self-report vs physiological arousal as measures state anxiety [61][62][63][64] , and there is evidence that people tend to have fairly poor introspection into how much they are physiologically reacting to stressors 65 . Therefore, rather than deciding a priori on a single 'best' way to measure math-related state anxiety (i.e., in-the-moment anxiety associated with math), we instead measured multiple indices, including subjective self-report measures and several biological measures related to anxiety: heart rate (HR), skin conductance levels (SCL), and pre-ejection period (PEP).…”
Section: Resultsmentioning
confidence: 99%
“…Prior work, however, has shown inconsistent correlations between traditional (trait) math anxiety and various measures of in-the-moment ('state') anxiety about math 49 . Additionally, there is debate about the utility of self-report vs physiological arousal as measures state anxiety [61][62][63][64] , and there is evidence that people tend to have fairly poor introspection into how much they are physiologically reacting to stressors 65 . Therefore, rather than deciding a priori on a single 'best' way to measure math-related state anxiety (i.e., in-the-moment anxiety associated with math), we instead measured multiple indices, including subjective self-report measures and several biological measures related to anxiety: heart rate (HR), skin conductance levels (SCL), and pre-ejection period (PEP).…”
Section: Resultsmentioning
confidence: 99%
“…For example, previous laboratory studies showed that associations between subjective stress and heart rate peak during occurrence of stressors and that heart rate levels recover after five minutes [ 53 , 190 ]. This goes along with the recommendation of not using time frames of more than 30 minutes when examining cardiovascular outcomes [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are few exceptions with narrowed scope including a recent review targeting specific psychophysiological outcomes in psychiatric populations [ 63 ] and a review solely targeting cortisol reactions but missing a systematic literature search [ 15 ]. Furthermore, a very recent systematic review found mixed evidence regarding associations of perceived stress and cardiovascular reactions [ 64 ]. The authors of this study noted that blood pressure, heart rate and HRV were most often investigated and that perceived stress was operationalized in very different ways potentially explaining disparate findings [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations